Water-in-diesel emulsion, wide: characterization with an environmentally friendly surfactant - Farah Ezati, Saindi (2023)
Diesel engines are efficient and cost-effective, but their emissions contribute to environmental pollution and health concerns. Policies worldwide target reductions in CO, CO2, PM, and NO emissions from diesel exhaust. This study explores the potential of water-in-diesel emulsion (WiDE) as a sustainable fuel by incorporating an environmentally friendly surfactant derived from renewable raw material (RRM) namely UMPSA surfactant. In addition, physico-chemical characterization was done to evaluate the performance WiDE formulated with Triton X-100, Span 80 in compared to UMPSA surfactant. In this study. 2% UMPSA surfactant, 5% Span-80, and 5% Triton X-100 were used to emulsify 30% water into 70% diesel, creating WiDE with water as the continuous phase and diesel as the dispersed phase. The research findings highlight the potential of WiDE as sustainable fuel by employing RRM’s based surfactant while maintaining performance parity. This research breakthrough holds immense promise for advancing the development and adoption of WiDE as a viable and environmentally conscious alternative in the field of fuel technology.